Quality Control Analysis of Back Lock Product Using Six Sigma Method at PT Artria Widya - Annisa Zalna Saputri; Fahriza Nurul Azizah (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
A company intends to make the best quality of its product with the minimum number of product defects. This research was conducted to improve the quality of Back Lock products at PT Artria Widya to reduce the number of product defects produced. The Six Sigma method is a method that can improve the quality of a product, using the DMAIC approach, namely Define, Measure, Analyze, Improve, and Control. Based on the results of the research that has been done, it is known that the results of data processing obtained an average DPMO score of 160.179 with a sigma level of 5.12. At the analysis stage carried out using fishbone, there are two types of defects that most often occur, is silver and short. The proposed improvement actions are carried out using the 5W + 1H method which is expected to have zero defects. Setiap perusahaan pasti menginginkan kualitas produk yang diproduksinya terbaik dengan memiliki jumlah kecacatan produk seminimal mungkin. Penelitian ini dilakukan bertujuan untuk meningkatkan kualitas produk Back Lock di PT Artria Widya untuk mengurangi jumlah cacat produk yang dihasilkan. Metode Six Sigma menjadi salah satu metode yang dapat meningkatkan kualitas mutu suatu produk, dengan pendekatan DMAIC yaitu Define, Measure, Analyze, Improvement, dan Control. Berdasarkan hasil penelitian yang telah dilakukan diketahui bahwa hasil pengolahan data didapatkan skor rata-rata DPMO sebesar 160,179 dengan tingkat sigma 5,12. Pada tahap analisis dilakukan dengan menggunakan fishbone terdapat 2 jenis cacat yang paling sering terjadi yaitu silver dan short. Tindakan usulan perbaikan menggunakan metode 5W+1H yang diharapkan zero defect dapat terjadi.